Predictive value of HMGB1 for atrial fibrillation recurrence after cryoballoon ablation in paroxysmal atrial fibrillation patients. Issue 12 (20th September 2022) - Li, Xinxin; Zhao, Cuiting; Li, Meng; Yu, Hongxiao; Liu, Xiping; Zhu, Qing; Song, Xiaokun; Wang, Yonghuai; Yu, Bo; Ma, Chunyan
Abstract: Background: Cryoballoon ablation (CBA) is recommended for patients with symptomatic drug refractory paroxysmal atrial fibrillation (pAF). However, substantial atrial fibrillation (AF) recurrence is common during follow‐up. Searching for a potential biomarker representing both myocardial injury and inflammation to identify patients at high risk of AF recurrence after CBA is very meaningful for postoperative management of AF patients. Hypothesis: To evaluate the clinical efficacy of high‐mobility group box 1 (HMGB1) protein released from the left atrium to predict AF recurrence in pAF patients after CBA at 1‐year follow‐up. Methods: We included 72 pAF patients who underwent CBA. To determine the expression levels of HMGB1, left atrial blood samples were collected from the patients before CBA and after the procedure through the transseptal sheath. Patients were followed up for AF recurrence for 1 year. Results: A total of 19 patients of the 72 experienced AF recurrence. The level of postoperative HMGB1 (HMGB1post) was higher in the AF recurrence group than in the AF non recurrence group ( p  = .03). However, no differences were noted in the levels of other biomarkers such as preoperative high‐sensitivity C‐reactive protein (hs‐CRP), postoperativehs‐CRP, and preoperative HMGB1 between the two groups. Multiple logistic regression analysis revealed that a higher level of serum HMGB1post was associated with AF recurrence (odds ratio: 5.29 [1.17–23.92], p  = .04). Receiver operating characteristic analysis revealed that HMGB1post had a moderate predictive power for AF recurrence (area under the curve: 0.68; sensitivity: 72%; and specificity: 68%). The 1‐year AF‐free survival was significantly lower in patients with a high HMGB1post level than in those with a low HMGB1post level (hazard ratio: 3.81 [1.49–9.75], p  = .005). Conclusion: In pAF patients who under went CBA, the level of HMGB1 after CBA was associated with AF recurrence and demonstrated a moderate predictive power. Thus, we offer a potential biomarker to identify pAF patients at high risk of AF recurrence.